Healthy Leaders: Core Self-Evaluations Affect Leaders’ Health Behavior Through Reduced Exhaustion - Köppe, Christina; Schütz, Astrid (Frontiers in Psychology, 2019)
Leaders’ self-directed health behavior (i.e., SelfCare behavior) plays an important role in the health and well-being of both leaders and employees but has been neglected in research so far. This study was aimed at investigating the antecedents of SelfCare behavior in terms of the personal characteristics of the leaders. In a sample of 150 (98 male, 52 female) German leaders from a wide range of organizations, we examined the direct and indirect effects of core self-evaluations (i.e., CSEs) on leaders’ SelfCare behavior. We predicted that CSEs would be positively related to SelfCare behavior with reduced exhaustion as a mediator, and organizational health climate (i.e., OHC) as a moderator of this relationship. Results showed that CSEs were positively related to SelfCare behavior and that the reduced exhaustion mediated this relationship. There was no evidence that OHC moderated the positive relationship between CSEs and SelfCare behavior. Theoretical and practical implications of the study are discussed.